ANTIBACTERIAL n-HEXANE EXTRACT OF Uncaria Gambir Roxb FROM PONTIANAK: ANTIBAKTERI EKSTRAK n-HEXANE Uncaria Gambir Roxb DARIPONTIANAK - Desdy Hendra Gunawan; Iskandar, Dodi (PT. ROCE WISDOM ACEH, 2025)
Staphylococcus aureus is a Gram-positive bacterium that can act as both a commensal and an opportunistic pathogen, causing a range of infections from superficial skin conditions to life-threatening illnesses. The emergence of antibiotic-resistant strains, such as MRSA, highlights the need for alternative or complementary natural antibacterials. This study aimed to evaluate the antibacterial potential of n-hexane extract of Uncaria gambir Roxb (UGR) leaves against S. aureus through both in silico prediction and in vitro testing. The compounds present in the leaves were identified using the Knapsack family database and analyzed for antibacterial activity using PASS Online, while solubilitywas predicted with SwissADME. In vitro antibacterial activity was determined using the agar diffusion method at six extract concentrations (5–40%), with 10% Chloramphenicol as a positive control and sterile distilled water as a negative control. Results indicated that metabolites such as Gallic acid, Cinchonain Ia, and Procyanidins B1 and B3 exhibited the highest predicted antibacterial probabilities,with solubility patterns suggesting better extraction in nonpolar solvents. The inhibition zone diameter generally increased with extract concentration, reaching a maximum of 10.76 ± 1.58 mm at 40%, confirming a concentration-dependent effect. However, the extract’s activity remained lower than that of Chloramphenicol (20.47 mm). Factors such as low compound concentration, limited solubility, chemical properties, and bacterial defense mechanisms likely contributed to the moderate inhibitory activity of the compound. Overall, the n-hexane extract of Uncaria gambir leaves demonstrates measurable antibacterial potential against S. aureus, supporting its traditional use and indicating its promise for further study as a natural antibacterial agent.